Processamento sonoquímico de materiais mesoestruturados de óxido de zinco dopados com terras-raras - Costa, Bruna Carolina [UNESP] (2014)
The variety of tecnological applications related to semiconducting oxides-based devices has aroused great interest of the scientific community, making studies related to these materials expand greatly in recent years. Among these materials, zinc oxide (ZnO) is a semiconductor that has several properties which make it a potential material for applications in several areas, from light emitting diodes (LEDs0 to photvoltaic devices for solar cells. One factor that can influence of this material is doping. Particularly, lanthanide (known as rare earths) doping of ZnO, may offer unique opportunities for improvement in its photosensitive and photoelectrochemical properties. Thus, it has performed in this work, synthesis and characteristion of ZnO samples from sonochemical method, an assisted by ultrasound chemical synthesis method. An attempt to doping of the samples with rare-earth elements, in order to modify its optical properties and an investigation into the influences of ultrassonic treatment time on these samples were also performed. The obtained results suggest that the ultrasonic treatment acts as a catalyst for ZnO precipitation and has influences on the crystallinity and size of obtained structures. Furthermore, sonochemical synthesis method with use of a low power ultrassound irradiation, was not effective for rare earth elements incorporation in the ZnO matrix, since a surface and no significant incorporation was observed for samples synthesized in this work